Effect of higher driving frequencies in dual-frequency discharge on plasma generation in capacitive coupled plasmas: PIC-MCC simulation - Hiroshi Otomo; Jian-Syun Lai; Kunihiro Kamataki; Yuma Yamamoto; Masaharu Shiratani (AIP Advances)
We investigated the electron heating mechanism in dual-frequency discharge (DFD) with higher driving frequencies fH = 27.12 MHz (=2 fL) to 108.48 MHz (=8 fL) and fL = 13.56 MHz, focusing on electric field fluctuations and comparing the results with single-frequency discharge (SFD). In a typical DFD, fL is selected near the ion plasma frequency (e.g., 2 MHz) and is used to control ion behavior. However, this study explored the effects of setting fL to 13.56 MHz, exceeding the ion plasma frequency, on the electron heating process. Our results show that DFD achieves higher electron density per unit input power density compared to SFD. To investigate the underlying cause, we analyzed the spatiotemporal structure of the electric field and the auto-power spectrum of electric field fluctuations. DFD exhibited more electric field fluctuation peaks, including harmonics of fH and nonlinear coupling waves of fH and fL. These fluctuations were especially prominent in the sheath region, and the electric field fluctuation components in the frequency range up to the electron plasma frequency were larger in DFD than in SFD. In addition, the normalized electron power absorption densities were higher in DFD, indicating that large electric field fluctuations significantly contribute to electron heating, especially stochastic heating. This study highlights that electric field fluctuation analysis is a valuable tool for investigating electron heating mechanisms, particularly in the plasma sheath region, which plays a crucial role in plasma generation.